Current transformer performance in high voltage and low voltage systems - Abd Aziz, Muhammad Khairul Arifin (2008)
CmTent Transfonners (CT's) are instrument transfonners that are used to supply a reduced value of current to meters, protective relays, and other instruments. Current r transformer provide isolation fom the high voltage primary, permit grounding of the secondary for safety, and step-down the magnitude of the measured current to a value that can be safely handled by the instruments:'It is one of the critical protective devices in a high voltage substation and low voltage switch board. It is used as a sensor to detect faults that will generate signal to trip the protective relay. The performance of current transfonner is very impo11ant in preventive and predictive maintenance. It can reduce number of injury and minimize system and equipment failure as well as help to reduce the cost. In this work, the method of measu1ing and testing the electrical characteristics of CT's are first investigated and the experience gained in the measurement and testing are then used to check and verify the characteristics of CT's found the low voltage switchboard of the Electrical Installation lap. The procedures and steps involved in the measurement and testing are reported and discussed in this work. The method of measurement in the low voltage switchboard are also reported and discussed in this work